Diversity of Campylobacter spp. circulating in a rhesus macaque (Macaca mulatta) breeding colony using culture and molecular methods - Rebecca L. Bacon; Carolyn L. Hodo; Jing Wu; Shannara Welch; Colette Nickodem; Javier Vinasco; Deborah Threadgill; Stanton B. Gray; Keri N. Norman; Sara D. Lawhon (mSphere, 2024)
ABSTRACT Campylobacter jejuni and Campylobacter coli represent the leading causes of bacterial gastroenteritis in humans, and infections can produce post-infectious irritable bowel syndrome (PI-IBS). Rhesus macaques (Macaca mulatta) (RM) are similarly susceptible to acute campylobacteriosis and represent a potential model of PI-IBS. We characterized the Campylobacter species circulating in an RM breeding colony using culture, qPCR, and whole genome sequencing (WGS). We also compared the C. jejuni and C. coli prevalence in RM as detected with qPCR versus culture and identified risk factors for bacteria presence and intestinal disease. Culture of 275 samples yielded C. coli (103) and C. jejuni (8), of which 21.6% were resistant to quinolones and 3.6% were resistant to macrolides. Multidrug-resistant isolates were obtained exclusively from animals exhibiting diarrhea or with histologically confirmed chronic enterocolitis. WGS revealed a non-clonal population of Campylobacter spp. Genotypic predictions of resistance were excellent except for aminoglycosides. All sequenced isolates contained genes for all subunits of cytolethal distending toxin. qPCR detected a prevalence of 45.9% for C. coli and 29.6% for C. jejuni. The quantity of either bacteria was significantly higher (P < 0.05) in animals with intestinal disease compared to healthy animals, though only young age was significantly associated with the presence of Campylobacter sp. or intestinal disease. Significantly more C. jejuni positive animals were detected with qPCR than with culture. These results provide a comprehensive characterization of Campylobacter spp. circulating in a breeding colony of RM in the United States and suggest that qPCR is superior for the detection of C. jejuni in RM.IMPORTANCEGastrointestinal disease is one of the most common reasons for hospitalization in non-human primate colonies and accounts for over one-third of non-research related euthanasia. In rhesus macaques, this manifests as both acute diarrhea and chronic enterocolitis (CE), a syndrome of chronic diarrhea resulting in poor weight gain or weight loss which is minimally responsive to treatment. Campylobacter spp. are major causes of acute enterocolitis in rhesus macaques and may predispose individuals to the development of CE, similar to post-infectious irritable bowel syndrome in humans. Despite these concerns, there are few studies characterizing Campylobacter in rhesus macaque colonies, in particular utilizing whole genome sequencing and assessing findings with respect to the health status of the host. Our findings provide insight into Campylobacter strains circulating in rhesus macaque colonies, which can improve clinical monitoring, assist in treatment decisions, and provide new avenues of investigation into campylobacteriosis as a catalyst for CE.